Bioinspired Ultrathin Piecewise Controllable Soft Robots. Issue 5 (31st March 2021) - Li, Dengfeng; Wang, Song; He, Jiahui; Zeng, Hao; Yao, Kuanming; Gao, Zhan; Wu, Mengge; Liu, Yiming; Wang, Lidai; Xie, Zhaoqian; Yu, Xinge
Abstract: In nature, animals or plants often use soft organs to move and hunt. Research works on bioinspired materials and devices have attracted more and more interest as which show the potential for future intelligent robots. As key components of soft robots, biomimetic soft actuators are adapted to greater requirements for convenient, accurate, and programmable controlling robots. Here, a class of materials and processing routes of ultrathin actuators are reported for bioinspired piecewise controllable soft robots, where the actuators associate with thermal‐responsible soft silicone thin film with thickness as thin as 45 µm and electrically driven by well mechanical designed metallic thin film electrodes. Multiple electrodes in the robots in charge of individual segments control allow the soft robots exhibiting similar functionalities of animals or plants (for example, imitating the tongue of a reptile, such as chameleon to hunt moving preys, and mimicking vines to tightly wind around objects). These bionic results in the soft robots demonstrate their advantages in precise and flexible operation, which provides a good reference for the future research of intelligent soft actuators and robots. Abstract : Soft actuators often require accurate and programmable controlling abilities. Here, a bioinspired ultrathin piecewise controllable soft robot is developed. Multiple electrodes allow the robot exhibiting similar functionalities of animals or plants (imitating the tongue of a chameleon to hunt a moving ant, and mimicking vines to tightly wind around objects), which provides good references for future intelligent soft robots.